Presupposition Used in The Dialogue of The Main Character in The "How to Train Your Dragon: The Hidden World" Movie Script - Saputra, Yudi; Zaim, M (English Language and Literature, 2023)
This research aimed to find out the types of presupposition and also the function of the utterances that consist presupposition in main character (Hiccup) dialogues with other characters in that movie. This research conducted by using Yule (1996) theory about types presupposition and also by using Searle in Levinson (1983) about types of language function to analysed the data. From the main character utterance, the data collected with descriptive approaches and suitable with the context and identified them based on pragmatics aspect about presupposition. From 107 data, the researcher found 5 types of presupposition, those are existential presupposition, structural presupposition, lexical presupposition, factive presupposition and counter-factual presupposition. The dominant types of presupposition is lexical presupposition. The researcher also found the language function in each types of presupposition, the first one is from existential presupposition there are 3 language functions such as representative, directive and declarative, from structural presupposition, there are 3 language functions they are representative, directive and expressive, from factive presupposition, there are 3 language function they are representative, expressive and declarative, from lexical presupposition, there are 5 language function they are representative, directive, commissive, expressive and declarative, and from counter-factual presupposition, there are 2 language function they are representative and expressive. The dominant language function in each type of presupposition is representative language function.